Pendidikan Kesehatan dan Pendampingan Tentang Kekerasan Pada Perempuan dan Anak Menggunakan Daring di Rusun Cinta Kasih Kelurahan Cengkareng Timur - Novita, Regina Vidya Trias; Dewi, Ni Nyoman Sri Artina; Samosir, Martha Theresia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The COVID 19 pandemic situation has caused losses for many parties. Employees who are still working are forced to work from home which causes the intensity of meeting with the family to increase frequently, thus triggering tension stressors among family members. The reaction of family members such as running away from problems and blaming others. The output target of this activity is to carry out activities to increase knowledge about domestic violence and counselling. The implementation method consists of 2 phases of activity, namely counselling for family members who require consultation in the form of questions and answers about domestic violence and the extension phase using platform zoom. The result of the mean of knowledge level increased 55.2%, the health education was attended by 119 participants, and private consultation was served by 11 people for 3 days. Suggestions require commitment and cooperation from health workers, and cadres, in order to reach residents or communities who are victims or perpetrators as well as online counseling services.